Ca2Fe1.95Mg0.05O5: Innovative low cost cathode material for intermediate temperature solid oxide fuel cell. (13th July 2021) - Squizzato, E.; Carollo, G.; Glisenti, A.
Abstract: The good oxygen ion conductivity makes brownmillerites suitable as electrode materials for SOFCs. In this contribution, we focus on Ca2 Fe1.95 Mg0.05 O5 (CFMO) with the idea of evaluating this brownmillerite as a promising innovative and low-cost cathode material. The synthesis was made through citrate route, where a magnesium doping was carried out to emphasize Fe 3+ /Fe 4+ redox couple and thus the electronic conductivity. The chemical and physical properties of the material were verified by XRD, H2 -TPR, XPS, BET and SEM techniques. The material was electrochemically characterized as a cathode by EIS, obtaining promising ASR values (0.19 Ωcm 2 at 800 °C). Furthermore, CFMO stability under different atmosphere conditions was confirmed by EIS investigation at different oxygen partial pressures. The material was activated by deposition of FeOx nanoparticles through co-deposition and infiltration; the effect of increasing amount (10 and 15 wt %) was also studied. The Ca2 Fe1.95 Mg0.05 O5 based nanocomposites well perform as cathode materials and the electrocatalytic reduction of oxygen is enhanced by iron oxide. This is confirmed by a reduction of ASR to 0.17 Ωcm 2 at 800 °C for CFMO with Fe2 O3 15 wt % as the best result of the study. Graphical abstract: Image 1 Highlights: Cheap Brownmillerite based nanocomposites successfully synthetized by citrate route. Ca2 Fe1.95 Mg0.05 O3 activated by deposition of FeOx nanoparticles by coprecipitation and wet impregnation. Fe induced chemical capacitance observed and studied vs T and PO2 . ASR comparable to State-of-Art cathode (0.19 Ωcm 2 at 800 °C) is obtained. The best performance was achieved by 15% wt. Fe2 O3 infiltration (0.17 Ωcm 2 at 800 °C).